Association between neurodegenerative dementia and chronic rhinosinusitis: A nested case-control study using a national health screening cohort. Issue 36 (4th September 2020) - Wee, Jee Hye; Yoo, Dae Myoung; Byun, Soo Hwan; Hong, Seok Jin; Park, Min Woo; Choi, Hyo Geun
Abstract : Abstract: The aim of this case-control study was to evaluate the association between chronic rhinosinusitis (CRS) and neurodegenerative dementia in a large representative Korean population. The ≥ 50-year-old population was selected from the Korean Health Insurance Review and Assessment Service – National Sample Cohort from 2002 to 2015. A total of 17, 634 neurodegenerative dementia patients were matched in a 1:4 ratio with 70, 536 control participants for age, sex, income, and region of residence. Neurodegenerative dementia was defined using the ICD-10 codes G30 and F00. CRS was identified based on the ICD-10 code J32. Among the cohort, we selected participants who were treated ≥ 2 times and those who underwent head and neck computed tomography. The odds ratio (OR) for CRS in patients with dementia was analyzed using a conditional logistic regression model. Subgroup analyses were conducted according to age and sex. There was no difference in the prevalence of CRS with/without nasal polyps between the dementia (1.1%) and control (1.2%) groups ( P  = .825). CRS with/without nasal polyps was not significantly associated with dementia (adjusted OR = 0.96, 95% CI = 0.82–1.13, P  = .653). In the subgroup analyses according to age and sex, the adjusted ORs for CRS with/without nasal polyps were not higher in the dementia group than in the control group. Previous CRS was not associated with neurodegenerative dementia in the Korean population.